Renewable resources in an overlapping generations economy without capital - Erkki Koskela; Markku Ollikainen; Mikko Puhakka (Fondazione Eni Enrico Mattei (FEEM), 2000)
We incorporate a renewable resource into an overlapping generations model without capital and with quasi-linear preferences. Besides being an input for production the resource serves as a store of value. We characterise the dynamics, efficiency and stability of the steady state equilibria. The stability properties are sensitive to the type of resource growth. For constant growth there is only one steady state equilibrium which is stable and efficient. In the general case of the concave growth function there are usually at least two steady state equilibria, one of which is stable and the other one unstable. The unstable steady state is efficient, but the stable one may or may not be. We study the robustness of our results by assuming a logarithmic periodic utility function. If the stationary equilibrium is unique, it is stable regardless of whether the equilibrium is efficient or inefficient, and irrespective of the type of growth function. Our analytical results are illustrated by numerical calculations.
Keywords: D90; Q20; 330; Overlapping generations; renewable resources; Erneuerbare Ressourcen; Overlapping Generations; Theorie